9w+w+6w=

Simple and best practice solution for 9w+w+6w= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9w+w+6w= equation:


Simplifying
9w + w + 6w = 0

Combine like terms: 9w + w = 10w
10w + 6w = 0

Combine like terms: 10w + 6w = 16w
16w = 0

Solving
16w = 0

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Divide each side by '16'.
w = 0

Simplifying
w = 0

See similar equations:

| 5k-37=11(k+1) | | 71-6v-10v+32=-4v+7 | | (3+6)=3+(6) | | 5x+56+2x+82=180 | | 10v^3=90v | | 4h-7=12h+9 | | -2(5p+3)-3(p-6)= | | 2Y*3Y= | | 4d-5=-5 | | 5x+16+2x+82=180 | | -3x-9=-33 | | 6(2x-5)-4(x+2)-17x= | | 8x+27=5x+63 | | 2c-8=8 | | 16-32-2= | | (8+6)+4=8+(6+4) | | 2y-(-3)=-17 | | -16+-32-2= | | 8x-22=2x+4 | | 2v-(10)=16 | | 4y-5=9y+15 | | 3p-7=6p+8 | | -12m=-18 | | 40-3x-12=44+5x | | -3z-(10)=-17 | | 3x+5=-21-5-x | | 12j^2+11j=-2 | | -2v-(-1)=21 | | 3a-3=-18 | | -3c-10=14 | | 2x-4=3(x+4) | | 3x-(-9)=-18 |

Equations solver categories